2x(a+c)=

Simple and best practice solution for 2x(a+c)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(a+c)= equation:


Simplifying
2x(a + c) = 0
(a * 2x + c * 2x) = 0
(2ax + 2cx) = 0

Solving
2ax + 2cx = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2cx' to each side of the equation.
2ax + 2cx + -2cx = 0 + -2cx

Combine like terms: 2cx + -2cx = 0
2ax + 0 = 0 + -2cx
2ax = 0 + -2cx
Remove the zero:
2ax = -2cx

Divide each side by '2x'.
a = -1c

Simplifying
a = -1c

See similar equations:

| 3x^4-15x^3+6x^2-30x=0 | | 3x^4-15x^3+6x^2-30=0 | | 10d-15=12d | | x^4+2x^3+3x^2+18x-54=0 | | 3(x-7)+4(x+4)= | | -6y=24 | | -2(3-x)=30 | | .50y=1.5 | | 15a-2(4a+5)=-6a | | 3*12=.4y | | 10=5y-3y | | 6x-3x=12 | | -6(4-2x)=12x-24 | | 4x-3x=5 | | 2.5x+1.0x=7 | | 6x+33=5x | | 5m+3=18 | | -2n+3x=7 | | .50b+6=11 | | 8-x=12-2x | | b=9b-24 | | 9y^2-33y+24= | | -9+2(4g-7)=9 | | x+4=9-2x | | m+4+5=22 | | 33=x+4 | | z=1+i^12 | | 14+4=x+5x | | -160+-52x+1x^2+x^3=0 | | 5x(3x+5)=0 | | k^3-18k-7k^2=0 | | (3s+20)(s+1)=-22 |

Equations solver categories